2023
DOI: 10.1371/journal.pone.0283873
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human respiratory syncytial virus in Seoul, South Korea, during 10 consecutive years, 2010–2019

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections and hospitalization in infants and young children. Here, we analyzed the genetic diversity of RSV using partial G gene sequences in 84 RSV-A and 78 RSV- B positive samples collected in Seoul, South Korea, for 10 consecutive years, from 2010 to 2019. Our phylogenetic analysis revealed that RSV-A strains were classified into either the ON1 (80.9%) or NA1 (19.0%) genotypes. On the other hand, RSV-B strains demonstrated di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…Among all the studied respiratory viruses, RSV was the most frequently identified etiologic agent of ARIs during the 2022–2023 season and the second most commonly detected respiratory virus after SARS-CoV-2 during the previous two seasons. Temporal and geographic variations exist in the incidence of RSV infection, depending on the study population, detection methods, climate, and other factors ( Gimferrer et al, 2019 ; Valley-Omar et al, 2022 ; Bimouhen et al, 2023 ; Kim et al, 2023 ). During the COVID-19 pandemic, the intensity of the applied anti-epidemic measures has played a crucial role in determining the spread of seasonal respiratory viruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among all the studied respiratory viruses, RSV was the most frequently identified etiologic agent of ARIs during the 2022–2023 season and the second most commonly detected respiratory virus after SARS-CoV-2 during the previous two seasons. Temporal and geographic variations exist in the incidence of RSV infection, depending on the study population, detection methods, climate, and other factors ( Gimferrer et al, 2019 ; Valley-Omar et al, 2022 ; Bimouhen et al, 2023 ; Kim et al, 2023 ). During the COVID-19 pandemic, the intensity of the applied anti-epidemic measures has played a crucial role in determining the spread of seasonal respiratory viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis of RSV G genes revealed the presence of a 60-nucleotide duplication in HVR2, which is a landmark characteristic of BA strains initially described in Buenos Aires, Argentina, in 1999. Following its appearance, the BA genotype rapidly evolved and displayed significant diversification into at least 14 new genotypes ( Ábrego et al, 2017 ; Lee et al, 2021 ; Kim et al, 2023 ). Since 2006, RSV-B strains harboring this partial duplication have become globally predominant and have completely replaced all previously circulating RSV-B genotypes ( Trento et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The answer could be both. It has been established that the 2nd hypervariable region of G (HVR2) is highly variable and often used in determining RSV genotypes(51). However, in this study, we focused on a replication aspect starting with the polymerase L and observed variations majorly in the RdRP, CD, and MT domains.…”
Section: Discussionmentioning
confidence: 99%